2016
DOI: 10.1590/1982-0194201600003
|View full text |Cite
|
Sign up to set email alerts
|

Prevenção de recidiva de úlcera varicosa: um estudo de coorte

Abstract: Objective: Determine the relapse rate of varicose ulcer and check the association between relapse and prevention measures adopted. Methods: Cohort study involving 50 patients over 18 years of age post-healing of varicose ulcer monitored over ten years. Relapse was assessed through direct inspection during the clinical assessment, and the preventive measures used were informed by the patient. Pearson's chi-square test was used with p ≤0.05. Results: Relapse of varicose ulcer corresponded to 62.2%, mostly in wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
0
9
0
7
Order By: Relevance
“…Regarding compression therapy, one Brazilian study carried out with 50 patients older than 18 years with post-healing VU, monitored for ten years, showed that the most significant recurrence prevention measures were the use of elastic stockings, resting, and applying hydrating cream to the skin of the lower limbs (5) .…”
Section: They Recommended Physical Exercise But I Do Not Do It Becaumentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding compression therapy, one Brazilian study carried out with 50 patients older than 18 years with post-healing VU, monitored for ten years, showed that the most significant recurrence prevention measures were the use of elastic stockings, resting, and applying hydrating cream to the skin of the lower limbs (5) .…”
Section: They Recommended Physical Exercise But I Do Not Do It Becaumentioning
confidence: 99%
“…This condition requires interventions of specialized multidisciplinary teams able to develop care based on evidence and, at the same time, encourage individuals with VU in the adherence to care, thus contributing to co-responsibility (4) . Edema treatment has practical importance for VU healing and an appropriate compression therapy is considered gold standard for the care of this type of wound (1,(4)(5) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…parcial abandono do tratamento da lesão, bem como de orientações adequadas para o auto cuidado (PEREIRA et al, 2014;BORGES et al, 2016).…”
Section: Reas Revista Eletrônica Acervounclassified
“…CVD, including varicose veins and chronic venous insufficiency is one of the most common chronic medical condition, affecting around 5%-30% of adult population in the developed countries [9][10][11][12][13][14]. The sheer prevalence of varicose veins and substantial costs of treating late complications such as chronic ulcers contribute to a high burden on health systems, which accounts for a 1%-3% of total health care budget of many Western countries [15][16][17].…”
Section: Introductionmentioning
confidence: 99%